1999
DOI: 10.1097/00006254-199907000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Hepatitis in Pregnancy

Abstract: Fulminant hepatic dysfunction in the third trimester of pregnancy accompanied by fever may result from disseminated herpes simplex virus. Since 1969, 24 cases of herpes simplex hepatitis, including the current case, have been reported. Mucocutaneous lesions are present in only half of cases; therefore, suspicion for diagnosis of this disease is low. Twenty-five percent of cases were not diagnosed until autopsy. Maternal and perinatal mortality are high, approaching 39 percent for both mother and fetus. Early r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…13 After patients with immunosuppression, pregnant women are the largest group of adults with disseminated HSV infection; in one review, the mean gestational age at presentation was 31 weeks, and the case fatality rate was 39% for both mothers and neonates. 14 Other reviews have confirmed a high burden of HSV hepatitis among pregnant women 15,16 ; however, data on the incidence of primary HSV infection among pregnant women are limited. Recurrences of genital HSV infection increase in frequency during pregnancy, 17 although the clinical characteristics of recurrent genital HSV infection are similar in pregnant women and nonpregnant women.…”
Section: Pregnancy and Severity Of Infectionmentioning
confidence: 99%
“…13 After patients with immunosuppression, pregnant women are the largest group of adults with disseminated HSV infection; in one review, the mean gestational age at presentation was 31 weeks, and the case fatality rate was 39% for both mothers and neonates. 14 Other reviews have confirmed a high burden of HSV hepatitis among pregnant women 15,16 ; however, data on the incidence of primary HSV infection among pregnant women are limited. Recurrences of genital HSV infection increase in frequency during pregnancy, 17 although the clinical characteristics of recurrent genital HSV infection are similar in pregnant women and nonpregnant women.…”
Section: Pregnancy and Severity Of Infectionmentioning
confidence: 99%
“…Only 30–50% show characteristic herpetic skin lesions [37]. Laboratory investigations often show leucopenia, thrombocytopenia, and coagulopathy [36, 810]. Renal failure is not uncommon in these patients [5, 1114], and it has been shown to occur in up to 65% of patients with HSV-related ALF [3].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the maternal-placental interface appears to have fairly effective mechanisms to block the spread of HSV. Interestingly, even in cases with severe or disseminated maternal HSV infection during pregnancy, the fetus is often spared [84]. HSV DNA can be detected by PCR in a surprising proportion of placentas (roughly 10%) [85, 86].…”
Section: Epidemiology and Clinical Manifestations Of Neonatal Hsv mentioning
confidence: 99%